Engineering a stable CHO cell line for the expression of a MERS-coronavirus vaccine antigen - Nyon, Mun Peak; Du, Lanying; Tseng, Chien Te Kent; Seid, Christopher A.; Pollet, Jeroen; Naceanceno, Kevin S.; Agrawal, Anurodh; Algaissi, Abdullah; Peng, Bi Hung; Tai, Wanbo; Jiang, Shibo; Bottazzi, Maria Elena; et al. (Elsevier, 2018)
Middle East respiratory syndrome coronavirus (MERS-CoV) has infected at least 2040 patients and caused 712 deaths since its first appearance in 2012, yet neither pathogen-specific therapeutics nor approved vaccines are available. To address this need, we are developing a subunit recombinant protein vaccine comprising residues 377–588 of the MERS-CoV spike protein receptor-binding domain (RBD), which, when formulated with the AddaVax adjuvant, it induces a significant neutralizing antibody response and protection against MERS-CoV challenge in vaccinated animals. To prepare for the manufacture and first-in-human testing of the vaccine, we have developed a process to stably produce the recombinant MERS S377-588 protein in Chinese hamster ovary (CHO) cells. To accomplish this, we transfected an adherent dihydrofolate reductase-deficient CHO cell line (adCHO) with a plasmid encoding S377-588 fused with the human IgG Fc fragment (S377-588-Fc). We then demonstrated the interleukin-2 signal peptide-directed secretion of the recombinant protein into extracellular milieu. Using a gradually increasing methotrexate (MTX) concentration to 5 μM, we increased protein yield by a factor of 40. The adCHO-expressed S377-588-Fc recombinant protein demonstrated functionality and binding specificity identical to those of the protein from transiently transfected HEK293T cells. In addition, hCD26/dipeptidyl peptidase-4 (DPP4) transgenic mice vaccinated with AddaVax-adjuvanted S377-588-Fc could produce neutralizing antibodies against MERS-CoV and survived for at least 21 days after challenge with live MERS-CoV with no evidence of immunological toxicity or eosinophilic immune enhancement. To prepare for large scale-manufacture of the vaccine antigen, we have further developed a high-yield monoclonal suspension CHO cell line.